(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article analyzes the theoretical and practical aspects of the development of virtual pedagogical culture of parents. Also, the spiritual and moral issues related to the education of the younger generation through the development of virtual-pedagogical culture of parents, their solutions are widely covered.